Do lacunar strokes benefit from thrombolysis? Evidence from the Registry of the Canadian Stroke Network. (11th December 2012) - Shobha, Nandavar; Fang, Jiming; Hill, Michael D.
Abstract : Background: Lacunar infarcts constitute up to 25% of all ischaemic strokes. As acute intracranial vascular imaging has become widely available with computed tomographic angiography, thrombolysis of lacunar strokes has become contentious because an intracranial vascular lesion cannot be visualized. We studied the effect of thrombolysis on lacunar strokes compared to other clinical ischaemic stroke sub‐types. Methods: Ischaemic stroke patients from phase 3 of the Registry of the Canadian Stroke Network data (July 2003–March 2008) were included. Lacunar stroke was defined as a lacunar syndrome supported by computed tomography brain showing a subcortical hypodense lesion with a diameter <20 mm. Clinical syndromes were used to define other stroke sub‐types. The outcomes were mortality at 90 days, modified Rankin Scale score 0–2 at discharge, occurrence of intracranial haemorrhage as a complication of stroke in‐hospital, and discharge disposition to home. Results: A total of 11 503 patients of ischaemic stroke were included from the Registry of the Canadian Stroke Network 3 between July 2003 and March 2008. Lacunar strokes formed 19·1% of the total strokes. The total number of patients who received tissue plasminogen activator was 1630 (14·2%). A significant association was found between tissue plasminogen activator treatment and outcomes after controlling Oxfordshire Community Stroke Project types – for modified Rankin Scale at discharge and discharge to home, but not for mortality. A thrombolysis‐by‐Oxfordshire Community Stroke Project stroke sub‐type interaction was observed due to lack of benefit among the posterior circulation stroke sub‐types. Patients with lacunar strokes, partial anterior circulation stroke, and total anterior circulation strokes all benefited approximately equally from thrombolysis. Conclusions: Thrombolysis is associated with clinically improved outcome among patients with lacunar stroke syndromes.